2017
DOI: 10.17759/cpp.2017250203
|View full text |Cite
|
Sign up to set email alerts
|

Professionalization Of Empathy And Predictors Of Helping Professionals’ Burnout

Abstract: The article presents the results of a study of empathy in connection with the severity of symptoms of burnout among nurses. To assess empathy we used Interpersonal Reactivity Index (IRI) by M. Davis, to measure burnout level — Maslach Burnout Test (MBT). As a result of the regression analysis of the data, the main hypothesis of the study was confirmed: it is the level of personal distress as a phenomenon of empathy dysregulation that contributes to the development of symptoms of helping professionals’ burnout.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…However, our result also suggested that fantasy increased susceptibility to mental health symptoms, and this result was somewhat surprising, because fantasy is usually regarded as a cognitive component of empathy (Wu et al, 2012;Karyagina et al, 2017), and some previous research has found the positive function against mental health-related problems. For example, Karyagina et al (2017) have found that in nurses, both perspective taking and fantasy negatively correlated with professional burnout, which is also a typical index of mental health. However, in the present study, fantasy is proved to be a risk factor to mental health symptoms.…”
Section: Fantasy and Personal Distress Are Risk Factors To Preschool mentioning
confidence: 39%
See 1 more Smart Citation
“…However, our result also suggested that fantasy increased susceptibility to mental health symptoms, and this result was somewhat surprising, because fantasy is usually regarded as a cognitive component of empathy (Wu et al, 2012;Karyagina et al, 2017), and some previous research has found the positive function against mental health-related problems. For example, Karyagina et al (2017) have found that in nurses, both perspective taking and fantasy negatively correlated with professional burnout, which is also a typical index of mental health. However, in the present study, fantasy is proved to be a risk factor to mental health symptoms.…”
Section: Fantasy and Personal Distress Are Risk Factors To Preschool mentioning
confidence: 39%
“…However, in the present study, fantasy is proved to be a risk factor to mental health symptoms. An explanation is provided by the Karyagina et al (2017) study, which investigated the medical staff, who are often exposed to stronger emotional expressions, whereas the participants in this study were teachers whose working environment was different from that of the medical staff. Another recent research conducted in college sample also found that both fantasy and personal distress are negatively associated with neuroticism dimension in Eysenck Personality Questionnaire and positively correlated with the individual's trends of feeling anxiety and stress (Neumann et al, 2016).…”
Section: Fantasy and Personal Distress Are Risk Factors To Preschool mentioning
confidence: 99%
“…al. (2012) and showed that a higher level of job motivation of socionomy specialists prevents appearance of professional burnout, as well as by the work of Karyagina et. al.…”
Section: Correlations Of the Indicators Of Professional Orientation Of Socionomy Professionals And The Factors Influencing Successful Promentioning
confidence: 96%
“…Уровень выгорания находится в реципрокных отношениях со способностью к профессиональному использованию эмпатии в рамках помогающих профессий [24], а недостаток эмпатии, в свою очередь, негативно влияет на принятие диагностических решений [напр. , 25].…”
Section: профессиональное выгорание как практическая модель редукции субъективности из диагностических отношенийunclassified